Integrated physical-biochemical strategy to improve Valencia orange trees salinity resilience, yield and quality under saline irrigation - Hassan, Islam F.; Osmani, Mirsade; Gaballah, Maybelle S.; Brysiewicz, Adam; Kanwal Shahzadi, Aneela; Athar, Habib-ur-Rehman; Dalmaris, Eleftheria; El-Keblawy, Ali; Hatterman-Valenti, Harlene M. (Journal of Water and Land Development, 2026)
Saline irrigation is a major constraint to citrus production in semi-arid regions, where increasing groundwater salinity threatens long-term orchard sustainability. This study evaluated an integrated physical- biochemical strategy combining magnetically treated saline water (MTSW) with a foliar application of a seaweed- derived biostimulant (Ascophyllum nodosum) to mitigate salinity stress in Valencia orange (Citrus sinensis) grafted onto ‘Volkamer’ lemon (Citrus volkameriana). A two-year field experiment compared three irrigation regimes: nontreated saline water, MTSW alone, and MTSW supplemented with 10 cm3∙dm−3 of water and A. nodosum extract. The combined treatment significantly improved vegetative growth, leaf relative water content, and soluble carbohydrate accumulation, while reducing stress indicators including proline and malondialdehyde. Enhanced physiological status translated into higher fruit yield, greater juice percentage, and increased total soluble solids, accompanied by reduced titratable acidity relative to the saline control. Across both seasons, the integrated treatment consistently outperformed MTSW alone, indicating enhanced effects between altered water properties and biostimulant-mediated metabolic regulation. The results suggest that coupling magnetic water treatment with seaweed biostimulants strengthens osmotic adjustment, membrane stability, and carbon allocation under salinity stress. However, the experiment was unable to include a treatment combining saline irrigation with A. nodosum in the absence of magnetic treatment; therefore, the independent contribution of the biostimulant under non-magnetised saline conditions cannot be fully separated from the observed combined effects. Despite this limitation, the findings indicate that this chemical-free, field-validated approach provided a scalable management strategy to sustain citrus productivity and fruit quality under saline irrigation in arid and water-limited production systems.